2020
DOI: 10.7759/cureus.8524
|View full text |Cite
|
Sign up to set email alerts
|

Enterobius Vermicularis: A Parasitic Cause of Appendicular Colic

Abstract: Enterobius vermicularis is the most commonly identified parasite incidentally found within the appendix of a clinically diagnosed appendicitis. This parasitic cause of appendicular colic, primarily affecting children, is an important cause of negative appendicectomy. We report an unusual and interesting case of a young female who presented with clinical features of acute appendicitis. Laparoscopic appendicectomy revealed the presence of an Enterobius vermicularis infestation originating from the lumen of her v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Microscopic examination of Enterobius vermicularis specimens revealed acute inflammation in 10 (47.6%) specimens only. This finding is consistent with previous research done by Chitnis et al (2020).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Microscopic examination of Enterobius vermicularis specimens revealed acute inflammation in 10 (47.6%) specimens only. This finding is consistent with previous research done by Chitnis et al (2020).…”
Section: Discussionsupporting
confidence: 94%
“…Intestinal Enterobius vermicularis infections are the most frequent helminthic infections, affecting up to 200 million people worldwide and Enterobius vermicularis infections can mimic acute appendicitis (Chitnis et al, 2020;Sousa et al, 2021). In the present study, the most often reported parasite associated with acute appendicitis was Enterobius vermicularis, which was found in 21 (56.8%) of the specimens with parasitic infections and all patients had no mixed parasitic infections.…”
Section: Discussionmentioning
confidence: 99%
“…A notable case report describes a 17-year-old Caucasian female who presented with a classic picture of acute appendicitis. Intra-operatively, Enterobius vermicularis, commonly known as pinworm, was found obstructing and traversing the base of the appendix, underscoring the diverse array of etiological factors that can contribute to this condition [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…(tapeworm), Hymenolepis nana (dwarf tapeworm), Ascaris lumbricoides (roundworm), Trichuris trichiura (whipworm), Schistosoma haematobium, Schistosoma mansoni, Giardia lamblia, and the protozoan Entamoeba histolytica [165,166]. Such parasite infections may further cause appendicular colic [167] or appendicitis [167][168][169].…”
Section: Other Diagnoses Associated With the Vermiform Appendixmentioning
confidence: 99%